Metformin decreases bacterial trimethylamine production and trimethylamine N-oxide levels in db/db mice - Kuka, Janis (Sci Rep, 2020)
The current study aimed to explore whether metformin, the most widely prescribed oral medication for the treatment of type 2 diabetes, alters plasma levels of cardiometabolic disease-related metabolite trimethylamine N-oxide (TMAO) in db/db mice with type 2 diabetes. TMAO plasma concentration was up to 13.2-fold higher in db/db mice when compared to control mice, while in db/db mice fed choline-enriched diet, that mimics meat and dairy product intake, TMAO plasma level was increased 16.8-times. Metformin (250 mg/kg/day) significantly decreased TMAO concentration by up to twofold in both standard and choline-supplemented diet-fed db/db mice plasma. In vitro, metformin significantly decreased the bacterial production rate of trimethylamine (TMA), the precursor of TMAO, from choline up to 3.25-fold in K. pneumoniae and up to 26-fold in P. Mirabilis, while significantly slowing the growth of P. Mirabilis only. Metformin did not affect the expression of genes encoding subunits of bacterial choline-TMA-lyase microcompartment, the activity of the enzyme itself and choline uptake, suggesting that more complex regulation beyond the choline-TMA-lyase is present. To conclude, the TMAO decreasing effect of metformin could be an additional mechanism behind the clinically observed cardiovascular benefits of the drug.